Synaptic Potential and Plasticity of an SK2 Channel Gate Regulate Spike Burst Activity in Cerebellar Purkinje Cells - Ohtsuki, Gen; Hansel, Christian (iScience, 2018)
Neurons store information and participate in memory engrams as a result of experience-dependent changes in synaptic weights and in membrane excitability. Here, we examine excitatory postsynaptic potential (EPSP) amplitude and neuronal excitability in relation to these two mechanisms of plasticity. We analyze somato-dendritic double-patch recordings from cerebellar Purkinje cells while inducing intrinsic, SK2 channel-dependent plasticity or blocking SK channels with bath application of apamin. Both manipulations increase the build-up of EPSP amplitudes during an EPSP train and enhance the number of EPSP-evoked spikes, yielding insights into the mechanistic contribution of EPSP amplitude to single spikes and spike bursts. EPSP amplitude has an impact on whether spikes are fired or not, but direct measures of excitability (spike threshold/AHP) are better predictors of whether individual spikes or spike bursts are fired. Our findings show that Purkinje cell spiking is synaptically driven but that burst firing is gated by SK2 channel modulation and plasticity. [Display omitted] •The study is based on somato-dendritic double-patch recordings from Purkinje cells•Dendritically recorded EPSP amplitudes predict the occurrence of spike firing•Synaptic weight does not predict whether individual spikes or spike bursts occur•SK2 channel modulation/plasticity efficiently controls the spike output Neuroscience; Cellular Neuroscience; Specialized Functions of Cells